Pre‐ to postsleep change in psychophysiological reactivity to emotional films: Late‐night REM sleep is associated with attenuated emotional processing. (15th January 2015) - Werner, Gabriela G.; Schabus, Manuel; Blechert, Jens; Kolodyazhniy, Vitaliy; Wilhelm, Frank H.
Abstract Rapid eye movement (REM) sleep has been postulated to facilitate emotional processing of negative stimuli. However, empirical evidence is mixed and primarily based on self‐report data and picture‐viewing studies. This study used a full‐length aversive film to elicit intense emotion on one evening, and an emotionally neutral control film on another evening while psychophysiological and experiential responses were measured. Subsequent sleep was monitored polysomnographically, and specific film scenes were presented again on the next morning. Correlation analyses revealed that participants with longer late‐night REM sleep after the aversive film showed higher increase of electrodermal reactivity and less reduction of facial corrugator muscle reactivity to negative film scenes on the next morning. This indicates that REM sleep may be associated with attenuated emotional processing of prolonged and intense emotional stimuli from pre‐ to postsleep.